Ultrasound in the treatment of ischaemic stroke - Daffertshofer, Michael; Hennerici, Michael G. (The lancet, 2003)
Intravenous alteplase (recombinant tissue plasminogen activator) has been shown to be beneficial within a short 3 h window after stroke. Ultrasound has a thrombolytic capacity that can be used for pure mechanical thrombolysis or improvement of enzyme-mediated thrombolysis. Mechanical thrombolysis with ultrasound needs high intensities at the clot (>2 W/cm2) that may have unwanted side-effects, whereas improvement of enzymatic thrombolysis can be done at the safer energy levels used in diagnostic ultrasound. Methods of improving enzymatic thrombolysis with ultrasound include intra-arterial delivery of thrombolytic agents with an ultrasound-emitting catheter and targeted and non-targeted non-invasive transcranial ultra sound delivery during intravenous thrombolytic infusion. Animal and clinical studies of sonothrombolysis have shown clot lysis and accelerated recanalisation of arterial occlusion has been seen in in vitro flow models, occluded peripheral and coronary arteries, and intracerebral arteries. Controlled clinical trials to test safety management and effectiveness of both strategies are in progress.